A Model Of Christian Family Custody In South West Papua Province - Leuwol, Natasya Virginia; Watak, Skivo Reiner; Solissa, Ferdinando (Riwayat: Educational Journal of History and Humanities, 2025)
In the Southwest Papua Province, where traditional customs and Christian beliefs coexist, the goal of this study is to develop a model of Christian family foster care that is sensitive to cultural and spiritual differences. The study examines the ways in which Christian principles and regional customs are integrated to settle family parenting disputes, particularly those pertaining to marriage, childrearing, and family dispute resolution. The study uses focus groups, case studies, interviews with church leaders, community elders, and families, and a qualitative methodology.According to research, the sanctity of marriage, respect for parents, and harmony within the community serve as the cornerstones of Christian family foster care in Southwest Papua.The main focus of this research is the maintenance of family ties. The model created in this study outlines key ideas, such as the importance of public involvement in decision-making about nursing, how the church works to resolve conflicts, and how Christian teachings can be integrated with conventional wisdom. In addition, the model identifies problems, such as possible conflicts between Christian doctrine and customs, and then provides solutions to balance these elements. This study enhances our knowledge of how Christian teachings are contextualized in indigenous cultures and provides useful recommendations for families, legislators, and church leaders in Southwest Papua. To ensure that family-care procedures in this area are appropriate from a cultural and spiritual point of view, advancing the well-being of children and family stability, the proposed model provides a framework.